What mode of supply will matter the most for the future of services trade? - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2024)
This Policy Brief looks at the latest trends in services trade and tries to show their importance, in its various manifestations, for virtually all countries in the world. The paper starts with a short history of trade in services across centuries. Fast forward to today's realities, the paper uses the most comprehensive datasets documenting the latest trends in global trade in services by modes of supply, trying to fill a gap in trade policy analysis and providing new insights on the importance of different modes of supply for various countries. The paper concludes with some recommendations aimed at creating a bridge between the various policy priorities shaping the future of globalisation in coming years.
Keywords: 330; Dienstleistungshandel; Handelsgeschichte; Dienstleistung; Internationaler Tourismus; Transportgewerbe; Multinationales Unternehmen; Unternehmensdienstleistung; Welt